Associations of dietary riboflavin intake with coronary heart disease in US adults: a cross-sectional study of NHANES 2007–2018 - Qiqi Jin; Shanjiang Chen; Xiaojun Ji (Frontiers in Nutrition)
ObjectiveThere is currently little study on the relationship between dietary riboflavin intake and coronary heart disease (CHD) risk.MethodsUsing information from the National Health and Nutrition Examination Survey (NHANES) between 2007 and 2018, we carried out a cross-sectional study. Dietary riboflavin intake and CHD risk were examined using weighted univariate and multivariable logistic regression. To learn more about the connection between dietary riboflavin intake and CHD risk, subgroup analyses and interactions were conducted. Next, the potential non-linear association was visually described using restricted cubic spline (RCS).ResultsThe risk of CHD was inversely correlated with dietary riboflavin consumption. The multivariable odds ratio (OR) with 95% confidence interval (CI) for the risk of CHD was 0.52 (95%Cl: 0.34–0.81, Ptrend = 0.009) for the highest vs. lowest tertiles of riboflavin. This protective effect of dietary riboflavin on CHD was influenced by gender, drinking status and serum folate concentration. A non-linear inverse connection (Pfor nonlinearity ≤ 0.001) was shown using RCS analysis between riboflavin intake and the risk of CHD.ConclusionOur research suggested that consuming more riboflavin in your diet may lessen the risk of CHD. The results improved the current knowledge base and supplied potential implications for dietary recommendations and health policy.